ANALISIS KETERLAMBATAN PENYELESAIAN REPARASI KAPAL DENGAN METODE FAULT TREE ANALYSIS (SPOB Messi Kianna 1) - Rr ayu Pranita Wardhani; Yesica Novita Devi; Ambikka . (Proceeding Maritime Business Management Conference, 2024)
Ships play a crucial role in transportation in Indonesia, especially cargo ships that facilitate the distribution of goods between islands as well as imports and exports. The maintenance and repair process of ships is key to enhancing the performance and quality of shipping. Time is a critical factor in ship repair projects, measured by the timely completion of contracts. Proper project planning based on field conditions is essential to avoid problems. Analyzing project delays and applying methods such as Fault Tree Analysis (FTA) are necessary to improve project management efficiency, particularly in the repair of the SPOB Messi Kianna 1 vessel at PT. Dumas Tanjung Perak Shipyards. The researcher's goal in choosing this topic is to identify the factors causing delays in ship repair work. The probability values for each delay factor using the FTA method show that the preparation work has a probability of 0.00733.